2021
DOI: 10.3389/fonc.2021.663263
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an m6A-Related lncRNA Signature for Predicting the Prognosis in Patients With Kidney Renal Clear Cell Carcinoma

Abstract: PurposeThis study aimed to construct an m6A-related long non-coding RNAs (lncRNAs) signature to accurately predict the prognosis of kidney clear cell carcinoma (KIRC) patients using data obtained from The Cancer Genome Atlas (TCGA) database.MethodsThe KIRC patient data were downloaded from TCGA database and m6A-related genes were obtained from published articles. Pearson correlation analysis was implemented to identify m6A-related lncRNAs. Univariate, Lasso, and multivariate Cox regression analyses were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 31 publications
(36 reference statements)
1
51
0
Order By: Relevance
“…Weighted gene co-expression network analysis (WGCNA) was developed by Horvath and Zhang in 2005 ( 20 ). At present, WGCNA is becoming a powerful approach to detecting gene modules, exploring the correlation of the modules and phenotypes, and discovering hub genes that regulate critical biological processes ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Weighted gene co-expression network analysis (WGCNA) was developed by Horvath and Zhang in 2005 ( 20 ). At present, WGCNA is becoming a powerful approach to detecting gene modules, exploring the correlation of the modules and phenotypes, and discovering hub genes that regulate critical biological processes ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…m6A-related lncRNAs demonstrated promising roles in tumor diagnosis, prognosis, and treatment. Yu et al constructed an m6A-related lncRNA signature which could accurately predict the survival of kidney renal clear cell carcinoma patients (24). Moreover, m6A regulators also demonstrated potential therapeutical roles in disease treatment (25), such as FTO inhibitors MO-I-500 (26) and FB23-2 (27).…”
Section: Introductionmentioning
confidence: 99%
“…The areas under the ROC curves of the survival model for predicting 3-, 5-, 7-, and 10-year survival rates were 0.734, 0.752, 0.763, and 0.787, respectively, indicating that the risk model had a high predictive value (Figures 7E-H). Survival probability predicted by our angiogenesis prognostic signature was superior to the m6A-related lncRNA signature constructed by Yu et al (25) and the seven-MDEG signature constructed by Hu et al (26). For the patients with KIRC whose survival time was 1-4-years, our prognostic signature also showed a higher predictive accuracy compared with the autophagy-related long non-coding RNA signature constructed by Yu et al (24).…”
Section: Construction Of a Risk Model Using The Lasso-cox Regression Analysismentioning
confidence: 66%
“…Currently, other predictors of risk or survival based on different mechanisms or aspects do exist for KIRC. For example, Yu et al constructed two prognostic signatures on the basis of autophagy-associated long non-coding RNAs (lncRNA) and m6A-related lncRNAs, respectively, both of which could effectively predict the outcome of patients with KIRC (24,25). In another study, a 7-methylated differentially expressed gene signature was found to be a powerful prognostic factor for these patients (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation